2008
DOI: 10.1063/1.2830991
|View full text |Cite
|
Sign up to set email alerts
|

Cascade single-chip phosphor-free white light-emitting diodes

Abstract: In order to resolve the problems existing in the conventional phosphor-converted light-emitting-diodes (LEDs) and red-green-blue LEDs, the cascade single-chip phosphor-free white LED was proposed with GaAs∕GaN heterojunction direct wafer bonding. Corresponding to the color-matching calculation, the white LED demonstrated the CIE chromaticity coordinates of about (0.3, 0.3) at 20mA, which was very close to the ideal white light position (1∕3, 1∕3) on the chromaticity diagram. The fabrication and the electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…It was reported that after laser lifting the sapphire substrate of a blue LED, a green LED was bonded with the blue LED [15]. Also, X. Guo et al developed a method by wafer bonding an InGaN-based blue LED with an AlGaInP-based red LED to form the white-light device with blue and red emissions [16], which presented perfect CIE chromaticity coordinates near to (0.3, 0.3) at the injection current of 20 mA.…”
Section: Review Of Phosphor-free Monolithic White Light Ledsmentioning
confidence: 98%
See 2 more Smart Citations
“…It was reported that after laser lifting the sapphire substrate of a blue LED, a green LED was bonded with the blue LED [15]. Also, X. Guo et al developed a method by wafer bonding an InGaN-based blue LED with an AlGaInP-based red LED to form the white-light device with blue and red emissions [16], which presented perfect CIE chromaticity coordinates near to (0.3, 0.3) at the injection current of 20 mA.…”
Section: Review Of Phosphor-free Monolithic White Light Ledsmentioning
confidence: 98%
“…For stripe patterns, as reported by K. Hiramatsu et al, the SAE of GaN with stripe patterns oriented along different directions are inclined and bound by different semipolar planes. When the GaN was selectively grown on the SiO 2 stripes along the [11][12][13][14][15][16][17][18][19][20] direction for different growth temperatures and reactor pressures, {1-101} surfaces without or with narrow (0001) appeared, the growth rate of {1-101} was almost constant and independent of the growth conditions. As for the SAE GaN on the stripes along direction, Fig.…”
Section: Growth Of Gan Microfacets Using Selective Area Epitaxy and Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches have been proposed to fabricate single-chip white LEDs without using phosphors for the phosphors covered LEDs suffer from lower efficiency and the multi-chip LEDs have the disadvantages of assembling complication [1][2][3]. A prospective approach for obtaining phosphor-free single-chip white LEDs is using GaN-based irregular multiple quantum well (IMQW) structures, which have been reported in our previous works [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…Several techniques have since been proposed for generation of phosphor free white LEDs. Huang et al has generated white emission using pre-strained growth of InGaN/GaN quantum wells (QWs) [4] while Guo et al has used a single cascade LEDs chip consisting of InGaN and AlGaInP multiple quantum wells (MQWs) based LEDs integrated by wafer bonding [5]. This technique required additional wafer bonding step and the degradation of the two materials system may differ with usage leading to change in color quality with time.…”
mentioning
confidence: 98%